Y2O3:Eu3+ (5 mol%) with Ag nanoparticles prepared by citrate precursor - Ferrari, J. L. [UNESP]; Cebim, Marco Aurelio [UNESP]; Pires, Ana Maria [UNESP]; Couto dos Santos, M. A.; Davolos, Marian Rosaly [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
Y2O3:Eu3+ (5 mol% Eu3+) and Y2O3:Eu3+ (5 mol% Eu3+) containing 1 mol% of Ag nanoparticles were prepared by heat treatment of a viscous resin obtained via citrate precursor. TEM and EDS analyses showed that Y2O3:Eu3+ (5 mol% Eu3+) is formed by nanoparticles with an average size of 12 nm, which increases to 30 nm when Ag is present because the effect of metal induced crystallization occurs. Ag nanoparticles with a size of 9 nm dispersed in Y2O3:Eu3+ (5 mol% Eu3+) were obtained and the surface plasmon effect on Ag nanoparticles was observed. The emission around 612 nm assigned to the Eu3+ (D-5(0) -> F-7(2)) transition enhanced when the Ag nanoparticles were present in the Y2O3:Eu3+ luminescent material. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Yttrium oxide; Europium ion; Ag nanoparticles; Luminescence spectroscopy